2010
DOI: 10.2337/dc09-2090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Look AHEAD Study Intervention on Medication Use and Related Cost to Treat Cardiovascular Disease Risk Factors in Individuals With Type 2 Diabetes

Abstract: OBJECTIVETo examine the effect of a lifestyle intervention to produce weight loss and increased physical fitness on use and cost of medications to treat cardiovascular disease (CVD) risk factors in people with type 2 diabetes.RESEARCH DESIGN AND METHODSLook AHEAD is a multicenter randomized controlled trial of 5,145 overweight or obese individuals with type 2 diabetes, aged 45–76 years. An intensive lifestyle intervention (ILI) involving group and individual meetings to achieve and maintain weight loss through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
81
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 23 publications
4
81
0
Order By: Relevance
“…Weight loss interventions can reduce concomitant medication use and overall cost. [22][23][24] This study replicated and expanded our original behavioral intervention research, 25 which added to the literature with a longer 12-month intervention and focus on veterans with APD-associated obesity.…”
Section: Introductionmentioning
confidence: 65%
“…Weight loss interventions can reduce concomitant medication use and overall cost. [22][23][24] This study replicated and expanded our original behavioral intervention research, 25 which added to the literature with a longer 12-month intervention and focus on veterans with APD-associated obesity.…”
Section: Introductionmentioning
confidence: 65%
“…77 The one-year results of Look AHEAD demonstrate that intensive lifestyle intervention results in clinically significant weight loss in people with type 2 diabetes which is associated with improved diabetes control and cardiovascular risk factors and, at the same time, reduced medication use and cost. 78 Several further years are needed to determine whether the initial weight loss can be maintained, whether intentional weight loss has a long-term effect on risk factors, and whether the weight loss reduces cardiovascular mortality and morbidity. 78,79 Li et al reported 20-year follow-up results on incidence of type 2 diabetes and cardiovascular disease from the China Da Qing Diabetes Prevention Study 80 and found that the reduction in diabetes incidence persists in the combined intervention group, which is also supported by the findings from the Finnish Diabetes Prevention Study 81 (with seven years of follow-up).…”
Section: Clinical Trials On Prevention and Treatment Of Diabetic Vascmentioning
confidence: 99%
“…78 Several further years are needed to determine whether the initial weight loss can be maintained, whether intentional weight loss has a long-term effect on risk factors, and whether the weight loss reduces cardiovascular mortality and morbidity. 78,79 Li et al reported 20-year follow-up results on incidence of type 2 diabetes and cardiovascular disease from the China Da Qing Diabetes Prevention Study 80 and found that the reduction in diabetes incidence persists in the combined intervention group, which is also supported by the findings from the Finnish Diabetes Prevention Study 81 (with seven years of follow-up). However, whether lifestyle intervention also leads to reduced cardiovascular disease and mortality remains unclear.…”
Section: Clinical Trials On Prevention and Treatment Of Diabetic Vascmentioning
confidence: 99%
“…2 Studies show that lifestyle and self-management support, such as physical activity and proper nutrition, play a critical role in the prevention and treatment of type 2 diabetes and in a patient's overall health. [3][4][5][6][7][8][9][10] Yet health care providers do not have the time-nor is it their job-to provide this form of ongoing and comprehensive self-management support for their patients.…”
Section: Introductionmentioning
confidence: 99%